Silo-best for corn silage - K. Bolsen; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1980)
Two corn silages (37 to 38% DM) were made September 2 and 3, 1975; one was ensiled without additive (control), the other with Silo-Best added at 1.0 lb. per ton of fresh crop. Silos were opened after 36 days, and each silage was full-fed to 15 yearling steers (3 pens of 5 steers) during an 87-day trial (October 10, 1975, to January 5, 1976). Complete-mixed rations contained 86% silage and 14% soybean meal supplement on a DM basis.
Keywords: Cattlemen' s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Corn silage; Additive; Soybean meal